Condicionantes ambientais da variação espacial da comunidade de anuros em uma área de arbustal antropizada no Pantanal Norte - Ardevino Filho, Marcos Antonio Gonçalves (2013)
Anuran communities can be structured and regulated by factors related to environmental conditions. The habitat heterogeneity is recognized as a key factor that positively affects the community structure of anurans. The diet is also one of the most important dimensions in the niche of anurans, being the main item arthropods, usually abundant and also influenced by the structure of the plant environment. The aim of this study was to understand the importance of habitat structure and food availability on community structure of anurans in areas of arbustal in the northern Pantanal. The data collection on community structure (richness, abundance, and composition) of anurans was conducted in September 2012, in ten plots, each about 100 m in length. Two collection methods were used: pitfall traps and active search. Variables to define the structure of the habitat (vegetation heterogeneity and complexity) and food availability (total biomass of arthropods) were collected. The relation of these variables with the community structure was verified from simple and multiple linear regressions. The composition of species was scaled from non-metric multidimensional scaling. We recorded 11 species belonging to five families. The richness and abundance of frogs did not vary with the vegetal heterogeneity and complexity, and food availability. The anurans composition varied according to the gradient of the vegetal heterogeneity and arthropods biomass. Shaded areas with more vegetal complexity did not affect the composition variation. In the present study, Leptodactylus elenae, species usually found in the forest formations in the Chaco and Pantanal, occurred in all sampling plots with high abundance. Although the results were not significant, species with foraging behavior of ambush predators seem to occur in areas with greater food availability, while wide foragers inhabit places with lower food availability, which deserves further investigation.